2013
DOI: 10.1016/j.neuropharm.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term CB1 receptor blockade enhances vulnerability to anxiogenic-like effects of cannabinoids

Abstract: Compelling evidence has documented the anxiolytic and mood-enhancing properties of cannabis. In susceptible users, however, consumption of this drug is conducive to panic, paranoia and dysphoria. We hypothesized that the up-regulation of CB1 receptors (CB1Rs) in select brain regions may enhance the vulnerability to cannabinoid-induced anxiety. To test this possibility, we assessed the behavioral impact of a potent cannabinoid agonist (CP55,940; 0.05–0.1 mg/kg, IP) on C57BL/6 male mice, respectively subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
1
10
1
Order By: Relevance
“…However, in contrast to the present findings, chronic adult AM-251 treatment has been previously reported to produce a negative correlation between PFC CB1R expression and time spent in the center of the elevated plus maze and stretch attend postures (Tambaro et al, 2013). Despite this, increased risk assessment following disruption of peri-adolescent eCB signaling in the current study is reminiscent of the effects of stress during adolescence, which has been shown to increase risk M A N U S C R I P T…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to the present findings, chronic adult AM-251 treatment has been previously reported to produce a negative correlation between PFC CB1R expression and time spent in the center of the elevated plus maze and stretch attend postures (Tambaro et al, 2013). Despite this, increased risk assessment following disruption of peri-adolescent eCB signaling in the current study is reminiscent of the effects of stress during adolescence, which has been shown to increase risk M A N U S C R I P T…”
Section: Discussioncontrasting
confidence: 99%
“…Chronic treatment with AM-251 in adult mice induced region-dependent differences in CB1R expression, with an upregulation in the PFC and striatum and downregulation in the hippocampus and mid-brain (Tambaro et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Experiment 1: long-term effects of AM251 and stress exposures in adolescence 4.1.1. Anxiety-like behaviours Endocannabinoid regulation of anxiety-like behaviours is welldocumented, although most investigations have involved the effects of agonism or antagonism while the drugs were in the system (Bellocchio et al, 2013;Bitencourt et al, 2008;Griebel et al, 2005;Haller et al, 2002Haller et al, , 2004Litvin et al, 2013;Moreira et al, 2008;Navarro et al, 1997;Rey et al, 2012;Rubino et al, 2008a;Simone et al, 2015a, b;Tambaro et al, 2013). In general, acute administration of CB1 receptor agonists decrease, whereas antagonists increase, anxiety-like behaviour in adult rats (Lafenetre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse tissues were homogenized in 50 mM Tris-HCl (pH 7.4), 150 mM NaCl, 1.0% (v/v) Triton X-100, 0.1% (w/v) SDS, and 10 mM EDTA supplemented with protease inhibitors as described previously (55). Brain samples were centrifuged for 30 min at 14,000 rpm (4°C), and then the supernatant was collected and stored at Ϫ20°C.…”
Section: Sds-page and Western Blottingmentioning
confidence: 99%